Ekstrak Solanum betaceum Mampu Meningkatkan Tebal Epitel dan Diameter Tubulus Seminiferus pada Mencit (Mus musculus) yang Terpapar Timbal Asetat - Nurul Fatimah Susanti; Reny I’tishom; Siti Khaerunnisa (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
One of the environmental factors that cause male infertility is heavy metal pollution such as lead. Lead can interfere with male fertility. Flavanoids are antioxidants that can prevent the negative effects caused by lead. The flavonoids contained in the Solanum betaceum extract have the potential to prevent the adverse effects of lead on the reproductive tract of mice because it can prevent oxidative stress. So it can affect the thickness of the seminiferous tubule epithelium and the diameter of the seminiferous tubules of mice exposed by lead acetat. The research method was a pure experimental laboratory (true experimental) randomized posttest only control group design approach. The total sample of 40 heads was divided into 5 groups. The study used 5 treatments. The concentration of Solanum betaceum for research group 100 mg/kg BW/day, 200 mg/kg BW/day, 400 mg/kg BW/day. Data analysis was performed analytically using One Way Anova. The results showed the mean ± standard deviation of the highest seminiferous tubular epithelium was highest 76.63 ± 7.17 and the mean ± standard deviation of the highest seminiferous tubule diameter was highest at 219.98 ± 17.06 in the P3 group. The results of this study indicate that there were significant differences between groups with p